2019
DOI: 10.1101/718684
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carotid intima-media thickness in UK Biobank: Identification of novel genome-wide loci, sex-specific effects and genetic correlations with obesity and glucometabolic traits

Abstract: Objectives: Atherosclerosis is the underlying cause of most cardiovascular disease, but mechanisms underlying atherosclerosis are incompletely understood. Ultrasound measurement of the carotid artery intima-media thickness (cIMT) can be used to measure vascular remodelling, which is indicative of atherosclerosis. Genomewide association studies have identified a number of genetic loci associated with cIMT, but heterogeneity of measurements collected by many small cohorts have been a major limitation in these ef… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 29 publications
1
24
0
Order By: Relevance
“…We replicated all SNPs associated with cIMT mean , and all except one (rs11025608) for cIMT max in a previous GWAS that used a proportion of the current UK Biobank samples. 13 We also confirmed 7 of 11 loci that were identified in the CHARGE/UCLEB consortia meta-analysis, including 31 studies with various study designs. 12 These include variants at ATP6AP1L, MCPH1, SGK223 (moderate LD of 0.267 between the 2 lead variants rs11785239 and rs2980478 near ZNF705B identified in the current analysis), ZHX2 , PINX1, CBFA2T3 , and APOE.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…We replicated all SNPs associated with cIMT mean , and all except one (rs11025608) for cIMT max in a previous GWAS that used a proportion of the current UK Biobank samples. 13 We also confirmed 7 of 11 loci that were identified in the CHARGE/UCLEB consortia meta-analysis, including 31 studies with various study designs. 12 These include variants at ATP6AP1L, MCPH1, SGK223 (moderate LD of 0.267 between the 2 lead variants rs11785239 and rs2980478 near ZNF705B identified in the current analysis), ZHX2 , PINX1, CBFA2T3 , and APOE.…”
Section: Discussionsupporting
confidence: 70%
“…Two loci 5q14.2 ( VCAN, HAPLN1 ) and 8p23.1 ( MCPH1 ) have been reported in previous sex-stratified analysis on cIMT mean. 13 Among the 5 new loci, 17p12 ( MAP2K4 / MYOCD ) were significantly associated with cIMT mean and cIMT max in females only, whereas associations at 14q32.13 ( SYNE3 ) and the 3 loci at 8p23.1 ( SOX7, GATA4/C8orf49, ZNF705B ) were only significant in males.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, participants with GG genotype had a prolonged QRS duration compared to those with CC genotype (89.00 ± 14.01 vs. 88.48 ± 14.44 ms) ( Supplementary Table 7 ), which was in accordance with the notion that each copy of C allele in rs4074536 was associated with less than 1 ms shortening of QRS duration ( Sotoodehnia et al, 2010 ). Interestingly, our PheWAS approach revealed that rs4484922 showed nominal evidence of association with multiple parameters of carotid intima-medial thickness (cIMT) ultrasound measurement ( Supplementary Table 7 ), and the elevated cIMT observed in individuals with CC genotype may increase the risk of atherosclerosis, which is an underlying cause of multiple CVDs ( Strawbridge et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Carotid intima-media thickness (CIMT) evaluation is a noninvasive and sensitive technique in detection and quantification of subclinical atherosclerosis (7). Also, CIMT is considered as a predictive factor of cardiovascular incidents.…”
Section: Introductionmentioning
confidence: 99%